Penggunaan Media BAP untuk Mendukung Keberhasilan Kultur Jaringan Wortel (Daucus carota) (Universitas PGRI Sumatera Barat, 2017)
Plant duplication through tissue culture is applied primarily to large exploited plants. Plant tissue culture was developed to help multiply the various types of plants, especially for plants that are difficult to be generatively cultivated. The purpose of this research is to know tissue culture technique at Carrot plant (Daucus carota) and to know the influence of BAP media on growth and development of plant carrot eksplan. The method used is experimental method with 4 treatments. The results showed that eksplan can not form the roots, stems, and leaves and callus there is only one repetition that can grow well. The percentage of plant tissue culture success using BAP media is 1%. This happens because of contamination